Aspek Hukum Perlindungan Konsumen Terhadap Peredaran Obat Keras di Pasaran: Studi pada Balai Besar Pengawas Obat Makanan (BB POM) Denpasar - E Sibuea, Joseph; Puspawati, I Gst. Ayu; Sutama, Ida Bagus Putu (Kertha Semaya : Journal Ilmu Hukum, 2015)
Different types of treatment are not always heal, even less so when using drugs does not fit precisely give rise to new disease. Because it is the above and the importance of the function of the drug, many people have abuse. Drugs that do not get permission from the Head BBPOM easily available at a price much more economical than the legal drugs that have received marketing authorization from the Head BBPOM. This study aims to determine the terms of drugs that may be enrolled in the Center for Food and Drug Administration (BBPOM) in Denpasar and BBPOM role in consumer protection with regard to dang drugs. The research method used is empirical jurisdiction. In order to realize a healthy society then, the terms listed drugs must have the name of the drug, which the registration, the existence of a generic name, and any trade names. Center for drug and food Supervisors have a role as an oversight and provide information to consumers on the hard drug.
Keywords: Central POM, Consumer, Dangerous Drugs